Anting Jepit Bunga Cosmos: Kreasi Perhiasan Berbahan Resin dan Bunga Kering - -, Chici Yuliana Nadi (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2024)
"Cosmos Flower Clip Earrings" are the creation of the Petrichor Project UMKM, which responds to consumer requests to create jewelry made from real flower petals. This research aims to determine the effect of differences in earring results using variations in UV (ultra violet) resin smeared techniques on pressed Cosmos flowers in the process of creating original flower petal earrings. The creation method used is an experimental method, with the independent variable being the UV resin application technique, and the dependent variable being pressed Cosmos flowers. The UV resin application technique is divided into two, namely the one-sided smeared technique and the two-sided cross smeared technique. The research data was then analyzed descriptively-qualitatively. There is a significant difference in the final result in the shape of the flower petals, where the one-sided smeared technique changes the shape of the flower petals from flat to curved. Both samples have the same luster, the flowers do not experience color deformation, and have good resistance to impact and scratches.